Gendered Subjects in Ottoman Constitutional Agreements, ca. 1740-1860 - Başak Tuğ (European Journal of Turkish Studies)
This article aims to historicize the notion of honor in the Ottoman legal discourse and practice from the early-modern period to the so-called “reform era”, the era most scholars maintain began with the Tanzimat Edict of 1839. Such a historical approach uses justice as a key to understand honor not as a value system, but as a rhetoric. Thus, it problematizes an a-historical conception of honor which assumes that honor codes in modern societies are largely the legacy of “traditional” norms of the pre-modern periods. This study argues that the persistent emphasis on honor in the correspondence especially between the central government and the Ottoman subjects in the eighteenth century reflects the development of new parameters between the state and its subjects in moral terms. On the one hand, the motto of “life, honor and property” of the Tanzimat Edict represents a continuation of such discourse of honor as a legitimizing mechanism. Yet, on the other hand, the legal codification of honor in the Criminal Codes of the nineteenth century reflects a novel constitutional construction of gendered citizenship around reproduction in the conjugal family through the partnership of the patriarchal state and the male subjects.